2020
DOI: 10.1111/eje.12580
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of preclinical simulation training for dental students using a new digital real‐time evaluation system

Abstract: Background With the rapid development of technology, traditional dental education has undergone a transition with the active incorporation of digital technology into curricula. DCARER is a recently developed digital real‐time evaluation system for the digital assessment of student preclinical simulation practice performance. The system provides supplementary feedback on process analysis in addition to an objective final result. This study evaluated the grading validity of the DCARER system and its effect on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…Additionally, some studies have reported usefulness of the digital educational device from standpoints of objective assessment. 8 , 9 , 10 , 11 , 12 , 13 Thus, the digital simulator would hold the promise of its great potential in dental education, however, it has not yet been widespread in dental schools in the world. 1 Majority is still the conventional simulator training, in which trainees cut artificial teeth attached on phantom head and teachers perform visual inspection to make assessment and instruction.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some studies have reported usefulness of the digital educational device from standpoints of objective assessment. 8 , 9 , 10 , 11 , 12 , 13 Thus, the digital simulator would hold the promise of its great potential in dental education, however, it has not yet been widespread in dental schools in the world. 1 Majority is still the conventional simulator training, in which trainees cut artificial teeth attached on phantom head and teachers perform visual inspection to make assessment and instruction.…”
Section: Introductionmentioning
confidence: 99%
“…These digital objective evaluation systems or equipment have provided quantitative evaluation data, which have not only reduced teachers’ subjective evaluation bias but also assisted students with important learning opportunities, thereby enabling them to critically self-assess themselves [ 15 ]. The application of medical clinical training simulators and digital evaluation systems in preclinical training and clinical skills competitions reflects the development trend of modern medical education [ 9 , 16 ]. The digital evaluation model adopted in the Guanghua Cup provided significant ideas for participating universities related to the reform of clinical medical education.…”
Section: Discussionmentioning
confidence: 99%
“…For cavity preparation, 80 % of the score originated from the referees’ evaluation and 20 % originated from the automatic score of the Digital Tooth Carving Evaluation System (Fair Grader 2000; Nissin Dental Products Inc., Kyoto, Japan) [ 8 ]. For ceramic crown or ceramic veneer preparation, 80 % of the score was from the referees’ evaluation and 20 % was from the Real-time Dental Training and Evaluation System (RDTES, Ai Zhixing, Dcarer, China) [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Weight value determination. Formula (8) was used to determine the weight values of indexes at all levels [20].…”
Section: () ()mentioning
confidence: 99%